HCV Ag quantification as a one‐step procedure in diagnosing chronic hepatitis C infection in Cameroon: the ANRS 12336 study. Issue 1 (15th May 2017) - Duchesne, Léa; Njouom, Richard; Lissock, Frédéric; Tamko‐Mella, Gishlaine Flore; Rallier, Sandrine; Poiteau, Lila; Soulier, Alexandre; Chevaliez, Stéphane; Vernet, Guy; Rouveau, Nicolas; Pawlotsky, Jean‐Michel; Girard, Pierre‐Marie; et al.
Abstract: Introduction : The diagnostic procedure for chronic hepatitis C infection (CHC) usually combines anti‐HCV antibody (HCV‐ Ab ) and HCV‐RNA measurement. Quantifying HCV core antigen (cAg) as a one‐step procedure could shorten the diagnostic process. We aimed to assess the performance of cAg quantification in diagnosing CHC and how it is influenced by concomitant HIV or HBV infections. Methods : The cAg was quantified by an automated assay (Abbott Diagnostics) in 465 HCV‐ Ab negative serum samples and 544 HCV‐RNA positive serum samples ( n  = 1009) collected in patients from the Pasteur Center in Cameroon, some of whom were infected by HBV or HIV. Its performance was evaluated in comparison to the gold standard (ELISA or PCR) by estimating its sensitivity (Se) and specificity (Sp), and by comparing the area under ROC (AUROC) curves in each patient population: HCV mono‐infected, HCV‐HBV and HIV‐HCV co‐infected. Results : Among the 465 HCV‐ Ab negative patients, 51 and 79 were HIV‐ and HBV‐infected, respectively, whereas among the 544 patients with CHC, 27 and 28 were HIV‐ and HBV‐infected, respectively. The Spearman ρ correlation coefficient between cAg and HCV‐RNA was 0.75 ( p  < 0.00001). The assay had a sensitivity of 95.7% (95% CI: 93.2–97.5) and a specificity of 99.7% (95% CI: 98.1–10) in diagnosing CHC, corresponding to an AUROC of 0.99 (95% CI: 0.98–1.0). Being HIV‐ or HBV‐infected did not impact the performance of cAg (Se = 96.4%, Sp = 96.2% and AUROC = 0.98 (95% CI: 0.95–1.0) in the HBV group, Se = 100%, Sp = 88.2% and AUROC = 0.99 (95% CI: 0.97–1.0) in the HIV group, p between AUROC = 0.69). Conclusions : The cAg quantification displayed a high specificity and sensitivity for the diagnosis of CHC in Cameroon, and its performance was not significantly modified by a concomitant HIV or HBV infection. In the context of CHC elimination on a global scale, using cAg quantification as a screening tool to directly identify CHC could be a reliable tool in a "test and treat" strategy.